Baltic, Slavic, Germanic - Kortlandt, Frederik (Baltistica, 2016)
The western Indo-European vocabulary in Baltic and Slavic is the result of an Indo-European substratum which contained an older non-Indo-European layer and was part of the Corded Ware horizon. The numbers show that a considerable part of the vocabulary was borrowed after the split between Baltic and Slavic, which came about when their speakers moved westwards north and south of the Pripet marshes. Germanic and Balto-Slavic were never contiguous Indo-European dialects at any stage of their prehistory.